Consideration of the seismic hazard on the land use planning of the Poas Canton, Costa Rica - Barrantes, Gustavo (2016)
To incorporate the seismic hazard assessment in the land use planning can be done using seismic methods and Geographic Information System (GIS), in order to avoid the use of simplifications provided in law. In this paper, we used the deterministic method for assessment of the seismic hazard in Poas County, Province of Alajuela, Costa Rica. Following this method, we identified the seismic sources that represent the main threat to the county, and the possible maximum magnitudes; the seismic attenuation, as well as the maximum acceleration values that were transformed into seismic intensity. The use of a GIS allowed the estimate of values in a 5x5 m mesh, in order to generate the seismic hazard maps at appropriate scale for the land use planning. The results have shown that the northern part of the County has a high seismic hazard (IMM IX) as well as San Pedro town, according to the worst scenario possible.